Verifying the feasibility of using Hand-Held X-ray fluorescence spectrometer to analyze Linqing brick: evaluation of the influencing factors and assessing reliability - Zexuan Chen; Long Zhang; Feng Hou; Jialiang Xie (Heritage Science, 2020)
Abstract Linqing brick is quite popular in Chinese history. Currently, identifying the origin of Linqing brick is an important issue to be studied in the field of archeology and architectural history in China. Hand-Held X-ray fluorescence (HH-XRF) spectrometry enables the in situ determination of the main elements in Linqing brick in a rapid non-destructive manner. HH-XRF is important in identifying the origin of Linqing brick. However, HH-XRF could be influenced by certain factors and may be capable of measuring only the element contents of the surface for the bricks in situ. The present study aimed to verify the reliability of HH-XRF and to systematically evaluate the different factors influencing measurement precision and accuracy so that scientific advice could be provided regarding the usage of HH-XRF for this application. Four experiments were performed to determine the influencing factors and assess the reliability through cross-validation using inductively coupled plasma optical emission spectrometry (ICP-OES). Finally, the influence of the different studied factors was studied, and the reliability of HH-XRF was ensured. The facts to consider about the measurement time, cross validation, criteria to select points, treat surface and getting final data and how to avoid the effect of rain, while using this method, are provided.